Designing a Video as a Tool to Promote Zoom Hotel Jemursari Surabaya to its Target Market - Rendy Darmawan (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This is a creative thesis report on a problem that Zoom Hotel Jemursari Surabaya has. Zoom Hotel Jemursari is located at Jl. Raya Jemursari Surabaya. As a hotel the main product of Zoom Hotel Jemursari is the rooms it provides for the guests. The main problem of this hotel regarding the salespersons have difficulties to convince the customers because they do not have a promotional tool that can support them to provide more interesting information about Zoom Hotel Jemursari. Regarding this problem, I decided to make a promotional video as the solution for this problems. However, due to current pandemic, this thesis would cover questionnaire for the data and/until the act of creating the storyline for the promotional video. This promotional video will be a beneficial tool for Zoom Hotel Jemrusari’s salespersons because this tool will support the salespersons to convince the customers by providing more interesting information using this promotional video. Keywords: Promotional tool, promotional video, storylines, questionnaire, USP, Hotel,